Ultrasound in the evaluation of thyroid nodules. - Conceição, Daiana Lopez (2023)
The ultrasound scan provides pertinent information about the thyroid, such as the characteristics of the gland and adjacent structures, and it is one of the first complementary exams in the research of a thyroid nodule. Ultrasound is a non-invasive procedure with considerable sensitivity, it evaluates the particularities of each suspicious image and considers whether there are risk factors indicative of malignancy, helping in the diagnostic investigation by proposing the therapeutic follow-up according to each case. The TI-RADS classification evaluates thyroid nodules using ultrasound and classifies findings according to the likelihood of malignancy.